An experimental approach to assess the combined effects of multiple stressors on a large vertebrate species - Enrico Pirotta; Catriona M. Harris; Lori H. Schwacke; Len Thomas; Jason B. Allen; Aaron A. Barleycorn; Marco Casoli; Jonathan Crossman; Laura Aichinger Dias; Laura Engleby; Erin LaBrecque; Jenny A. Litz; et al. (Conservation Biology, 2026)
The design of experiments to investigate the combined effects of multiple stressors requires exposing target organisms to multiple combinations of stressor doses. Concurrent manipulation of stressors is often infeasible with wildlife, but long‐lasting health effects allow individual health to be used as an integrator of prior stressor exposure. The population of bottlenose dolphins in Barataria Bay, Louisiana, experienced long‐lasting health effects after exposure to oil from the Deepwater Horizon spill. We investigated whether compromised health status affects dolphins’ ability to respond to other stressors, specifically vessel traffic, potentially leading to increased collision risk. We used this case study to develop a hypothesis‐driven experimental approach to assess the combined effects of multiple stressors in a large, long‐lived vertebrate species. We conducted controlled vessel approaches to test whether the health status of targeted dolphins affected their behavioral responses. Our results highlighted some effects of health, suggesting that oil spills may exacerbate the effects of other stressors in coastal populations. For example, lung disease was associated with a delayed dive response, which could affect the ability to vertically avoid vessels and lead to increased collision risk. However, health effects on response probability were overall smaller than anticipated, and other contextual variables (e.g., sex, age, calf presence, prior experience, and exposure context) contributed to response variability. Our work demonstrated the value of formalizing stressor interactions as multidimensional dose–response functions and showed the feasibility of an experimental, multiple‐stressor study in a wild system in which individual health status can be used as an integrator of prior stressor exposure. This approach has broad implications for other species that are difficult to handle experimentally. The quantification and management of the cumulative risk from multiple stressors on wildlife will require a combination of empirical and mechanistic approaches to inform long‐term, population consequences.

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Root tissue chemistry influences the formation and composition of new mineral-associated organic matter - Brian Rinehart; Joe P. Noel; Justin Allen; Joeri Kaal; Dave McNear; Hanna Poffenbarger (Soil Biology and Biochemistry, 2026)

Detrital zircon U Pb geochronology of Lower Permian sedimentary rocks of the southern Sydney Basin in southeastern Australia: Implications for provenance and basin evolution - Bo Yang; Yazhuo Niu; Sangmin Lee; Allen Nutman; Solomon Buckman; Brian G. Jones; G.R. Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Bias corrections for species- and source-resolved PM2.5 chemical transport model simulations using a geographically weighted regression - Ksakousti Skyllakou; Carlos S. Hernandez; Pablo Garcia Rivera; Brian Dinkelacker; Julian D. Marshall; C. Arden Pope; Allen L. Robinson; Spyros N. Pandis; Peter J. Adams (Atmospheric Environment, 2026)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Integration of crop modeling and sensing into molecular breeding for nutritional quality and stress tolerance - Jonathan Berlingeri; Abelina Fuentes; Earl Ranario; Heesup Yun; Ellen Y. Rim; Oscar Garrett; Alexander Howard; Mary-Francis LaPorte; Sassoum Lo; Duke Pauli; Jenna Hershberger; Mason Earles; et al. (Theoretical and Applied Genetics, 2025)
Integrating innovative technologies into plant breeding is critical to bolster food and nutritional security under biotic and abiotic stresses in changing climates. While breeding efforts have focused primarily on yield and stress tolerance, emerging evidence highlights the need to also prioritize nutritional quality. Advanced molecular breeding approaches have enhanced our ability to develop improved crop varieties and could be substantially informed by the routine integration of crop modeling and remote sensing technologies. This review article discusses the potential of combining crop modeling and sensing with molecular breeding to address the dual challenge of nutritional quality and stress tolerance. We provide overviews of stress response strategies, challenges in breeding for quality traits, and the use of environmental data in genomic prediction. We also describe the status of crop modeling and sensing technologies in grain legumes, rice, and leafy greens, alongside the status of -omics tools in these crops and the use of AI with directed evolution to identify novel resistance genes. We describe the pairwise and three-way integration of AI-enabled sensing and biophysically and empirically constrained crop modeling into breeding to enable prediction of phenotypic and breeding values and dissection of genotype-by-environment-by-management interactions with increasing fidelity, efficiency, and temporal/spatial resolution to inform selection decisions. This article highlights current initiatives and future trends that focus on leveraging these advancements to develop more climate-resilient and nutritionally dense crops, ultimately enhancing the effectiveness of molecular breeding.

Regional differentiation in somatic growth and maturation attributes for loggerhead sea turtles (Caretta caretta) in the Northwest Atlantic - Larisa Avens; Margaret M. Lamont; Allen M. Foley; Benjamin M. Higgins; Lyndsey N. Howell; Gretchen Lovewell; Donna J. Shaver; Brian A. Stacy; J. Shelby Walker; Jamie M. Clark; Amy A. Wallace; Hannah B. Vander Zanden (Marine Biology, 2025)

Thermal prospecting for lunar water with a percussive hot cone penetrometer - Eleanor Zimmermann; George Johnson; Travis Wavrunek; Brian Johnson; Jeffrey Allen; Timothy Eisele; Paul van Susante (Advances in Space Research, 2025)

Reconciling scale using the Resist-Accept-Direct (RAD) Framework to improve management of woody encroachment in grasslands - Rheinhardt Scholtz; Daniel R. Uden; Brady W. Allred; Victoria M. Donovan; Jeremy D. Maestas; Scott L. Morford; Matthew O. Jones; David E. Naugle; Samantha M. Cady; Dillon T. Fogarty; Alexander L. Metcalf; Brian Chaffin; et al. (Journal of Environmental Management, 2025)

Pre‐existing phytoplankton biomass concentrations shape coastal plankton response to fire‐generated ash leachate - Nicholas Baetge; Kimberly H. Halsey; Erin J. Hanan; Michael J. Behrenfeld; Allen J. Milligan; Jason R. Graff; Parker Hansen; Craig A. Carlson; Rene M. Boiteau; Eleanor C. Arrington; Jacqueline Comstock; Elisa R. Halewood; et al. (Limnology and Oceanography, 2025)
Climate‐driven warming is projected to intensify wildfires, increasing their frequency and severity globally. Wildfires are an increasingly significant source of atmospheric deposition, delivering nutrients, organic matter, and trace metals to coastal and open ocean waters. These inputs have the potential to fertilize or inhibit microbial growth, yet their ecological impacts remain poorly understood. This study examines how ash leachate, derived from the 2017 Thomas Fire in California and lab‐produced ash from Oregon vegetation, affects coastal plankton communities. Shipboard experiments off the California coast examined how pre‐existing plankton biomass concentrations mediate responses to ash leachates. We found that ash leachate contained dissolved organic matter (DOM) that significantly increased bacterioplankton specific growth rates and DOM remineralization rates but had a negligible effect on bacterioplankton growth efficiency, suggesting low DOM bioavailability. Furthermore, ash‐derived DOM had a higher potential to accumulate in high biomass water, where pre‐existing DOM substrates may better support bacterial metabolism. Ash leachate had a neutral to negative effect on phytoplankton division rates and decreased microzooplankton grazing rates, particularly in low biomass water, leading to increased phytoplankton accumulation. Nanoeukaryotes accumulated in low biomass water, whereas picoeukaryotes and Synechococcus accumulated in high biomass water. Our findings suggest that the influence of ash deposition on DOM cycling, phytoplankton accumulation, and broader marine food web dynamics depends on pre‐existing biomass levels. Understanding these interactions is critical for predicting the biogeochemical consequences of increasing wildfire activity on marine ecosystems.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Governance of a landscape: The role of formal and informal organizations - Hannah Legatzke; Brian C. Chaffin; Theresa M. Floyd; Simanti Banerjee; Sarah Church; Sabrina Gulab; Samantha Hamlin; Gwendwr R. Meredith; Alexander L. Metcalf; Holly K. Nesbitt; Emily Sutherland-Rowen; Daniel R. Uden; et al. (Journal of Environmental Management, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Mesoscale Brain Mapping: Bridging Scales and Modalities in Neuroimaging – A Symposium Review - Joshua K. Marchant; Natalie G. Ferris; Diana Grass; Magdelena S. Allen; Vivek Gopalakrishnan; Mark Olchanyi; Devang Sehgal; Maxina Sheft; Amelia Strom; Berkin Bilgic; Brian Edlow; Elizabeth M. C. Hillman; et al. (Neuroinformatics, 2024)
Advances in the spatiotemporal resolution and field-of-view of neuroimaging tools are driving mesoscale studies for translational neuroscience. On October 10, 2023, the Center for Mesoscale Mapping (CMM) at the Massachusetts General Hospital (MGH) Athinoula A. Martinos Center for Biomedical Imaging and the Massachusetts Institute of Technology (MIT) Health Sciences Technology based Neuroimaging Training Program (NTP) hosted a symposium exploring the state-of-the-art in this rapidly growing area of research. “Mesoscale Brain Mapping: Bridging Scales and Modalities in Neuroimaging” brought together researchers who use a broad range of imaging techniques to study brain structure and function at the convergence of the microscopic and macroscopic scales. The day-long event centered on areas in which the CMM has established expertise, including the development of emerging technologies and their application to clinical translational needs and basic neuroscience questions. The in-person symposium welcomed more than 150 attendees, including 57 faculty members, 61 postdoctoral fellows, 35 students, and four industry professionals, who represented institutions at the local, regional, and international levels. The symposium also served the training goals of both the CMM and the NTP. The event content, organization, and format were planned collaboratively by the faculty and trainees. Many CMM faculty presented or participated in a panel discussion, thus contributing to the dissemination of both the technologies they have developed under the auspices of the CMM and the findings they have obtained using those technologies. NTP trainees who benefited from the symposium included those who helped to organize the symposium and/or presented posters and gave “flash” oral presentations. In addition to gaining experience from presenting their work, they had opportunities throughout the day to engage in one-on-one discussions with visiting scientists and other faculty, potentially opening the door to future collaborations. The symposium presentations provided a deep exploration of the many technological advances enabling progress in structural and functional mesoscale brain imaging. Finally, students worked closely with the presenting faculty to develop this report summarizing the content of the symposium and putting it in the broader context of the current state of the field to share with the scientific community. We note that the references cited here include conference abstracts corresponding to the symposium poster presentations.

Abundance, production, and migrations of nesting green turtles at Rose Atoll, American Samoa, a regionally important rookery in the Central South Pacific Ocean - Shawn K. Murakawa; Alexander R. Gaos; Devin S. Johnson; Brian Peck; Mark MacDonald; Elyse Sachs; Frank Pendleton; Camryn D. Allen; Marylou K. Staman; Shelbie Ishimaru; Kyle S. Van Houtan; Alphina Liusamoa; et al. (Frontiers in Marine Science, 2024)
Sea turtles are a taxon of conservation concern and are highly migratory, exposing them to a variety of threats (e.g., fisheries bycatch, direct harvest) across their lifetime. Understanding the abundance of nesting females, hatchling production, and migratory movements - three of the most basic biological data needs for this species group - is imperative for population assessment. This study summarizes novel data most relevant to population assessments of the endangered central south Pacific (CSP) green turtle ( Chelonia mydas ) population, determined from annual rapid assessment surveys (mean survey duration=7.6 days year -1 , n=61 survey days over 8 nesting seasons) and satellite telemetry at Rose Atoll, American Samoa, from 2012 to 2019. A minimum of 138 unique females nested in the Rose Atoll National Wildlife Refuge (RANWR) over the study period with 218 total females observed. Satellite tracks of post-nesting females suggest Fiji (n=33/48, 70.2%) is the primary foraging ground for turtles nesting at RANWR, though other areas throughout the south Pacific Ocean are also important. Limited data suggest hatchling production was high (average hatching success=92.3%) and nest temperature data collected from 2017-2019 suggest primary sex ratios were likely balanced during this time. These are positive signs for the resilience of this nesting population, but climate change poses threats to RANWR and other low-lying tropical islands throughout the central south Pacific, as nesting areas are potentially exposed to beach erosion, tidal inundations, and increasing temperatures leading to sex bias and embryonic death.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

An expert‐based system to predict population survival rate from health data - Lori H. Schwacke; Len Thomas; Randall S. Wells; Teresa K. Rowles; Gregory D. Bossart; Forrest Townsend; Marilyn Mazzoil; Jason B. Allen; Brian C. Balmer; Aaron A. Barleycorn; Ashley Barratclough; Louise Burt; et al. (Conservation Biology, 2024)
Timely detection and understanding of causes for population decline are essential for effective wildlife management and conservation. Assessing trends in population size has been the standard approach, but we propose that monitoring population health could prove more effective. We collated data from 7 bottlenose dolphin ( Tursiops trun catus) populations in the southeastern United States to develop a method for estimating survival probability based on a suite of health measures identified by experts as indices for inflammatory, metabolic, pulmonary, and neuroendocrine systems. We used logistic regression to implement the veterinary expert system for outcome prediction (VESOP) within a Bayesian analysis framework. We fitted parameters with records from 5 of the sites that had a robust network of responders to marine mammal strandings and frequent photographic identification surveys that documented definitive survival outcomes. We also conducted capture–mark–recapture (CMR) analyses of photographic identification data to obtain separate estimates of population survival rates for comparison with VESOP survival estimates. The VESOP analyses showed that multiple measures of health, particularly markers of inflammation, were predictive of 1‐ and 2‐year individual survival. The highest mortality risk 1 year following health assessment related to low alkaline phosphatase (odds ratio [OR] = 10.2 [95% CI: 3.41–26.8]), whereas 2‐year mortality was most influenced by elevated globulin (OR = 9.60 [95% CI: 3.88–22.4]); both are markers of inflammation. The VESOP model predicted population‐level survival rates that correlated with estimated survival rates from CMR analyses for the same populations (1‐year Pearson's r = 0.99, p = 1.52 × 10 –5 ; 2‐year r = 0.94, p = 0.001). Although our proposed approach will not detect acute mortality threats that are largely independent of animal health, such as harmful algal blooms, it can be used to detect chronic health conditions that increase mortality risk. Random sampling of the population is important and advancement in remote sampling methods could facilitate more random selection of subjects, obtainment of larger sample sizes, and extension of the approach to other wildlife species.

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Effect of hypoxia duration and pattern on channel Catfish (Ictalurus punctatus) neuropeptide gene expression and hematology - Brian D. Ott; Dakoda O. Chisolm; Matt J. Griffin; Eugene L. Torrans; Peter J. Allen (Journal of Comparative Physiology B, 2023)

Communication in the science-policy interface: Evidence from a boundary organization in Nebraska, USA - Sechindra Vallury; Brian C. Chaffin; Samantha L. Hamlin; Craig R. Allen (Environmental Science & Policy, 2023)

A novel method for calculating the projected health and climate co-benefits of energy savings through 2050 - Parichehr Salimifard; Marissa V. Rainbolt; Jonathan J. Buonocore; Mahala Lahvis; Brian Sousa; Joseph G. Allen (Building and Environment, 2023)

Global biome patterns of the Middle and Late Pleistocene - Brian Huntley; Judy R. M. Allen; Matthew Forrest; Thomas Hickler; Ralf Ohlemüller; Joy S. Singarayer; Paul J. Valdes (Journal of Biogeography, 2023)
Our primary aim was to assess the hypothesis that distinctive features of the patterns of vegetation change during successive Quaternary glacial–interglacial cycles reflect climatic differences arising from forcing differences. We addressed this hypothesis using 207 half‐degree resolution global biome pattern simulations, for time slices between 800 and 2 ka, made using the LPJ‐GUESS dynamic global vegetation model. Simulations were driven using ice‐core atmospheric CO 2 concentrations, Earth's obliquity, and outputs from a pre‐industrial and 206 palaeoclimate experiments; four additional simulations were driven using projected future CO 2 concentrations. Climate experiments were run using HadCM3. Using a rule‐based approach, above‐ground biomass and leaf area index of LPJ‐GUESS plant functional types were used to infer each grid cell's biome. The hypothesis is supported by the palaeobiome simulations. To enable comparisons with the climatic forcing, multivariate analyses were performed of global vegetation pattern dissimilarities between simulations. Results showed generally similar responses to glacial–interglacial climatic variations during each cycle, although no two interglacials or glacials had identical biome patterns. Atmospheric CO 2 concentration was the strongest driver of the dissimilarity patterns. Dissimilarities relative to the time slice with the lowest atmospheric CO 2 concentration show the log‐linear relationship to atmospheric CO 2 concentration expected of an index of ecocarbon sensitivity. For each simulation, extent and total above‐ground biomass of each biome were calculated globally and for three longitudinal segments corresponding to the major continental regions. Mean and minimum past extents of forest biomes, notably Temperate Summergreen Forest, in the three major continental regions strongly parallel relative tree diversities, hence supporting the hypothesis that past biome extents played an important role in determining present diversity. Albeit that they reflect the climatic consequences only of the faster Earth system components, simulated potential future biome patterns are unlike any during the past 800 ky, and likely will continue to change markedly for millennia if projected CO 2 concentrations are realised.

Discovery of pyrrolo[2,1-f][1,2,4]triazine-based inhibitors of adaptor protein 2-associated kinase 1 for the treatment of pain - Carolyn D. Dzierba; Bireshwar Dasgupta; George Karageorge; Walter Kostich; Brian Hamman; Jason Allen; Kim M. Esposito; Ramesh Padmanabha; James Grace; Kimberley Lentz; John Morrison; Daniel Morgan; et al. (Medicinal Chemistry Research, 2023)

Food choice behavior of adolescents under parent-child interaction in the context of US school lunch programs - Thadchaigeni Panchalingam; Gregory Howard; H. Allen Klaiber; Brian E. Roe (Food Policy, 2023)

Physiological response of channel (Ictalurus punctatus) and hybrid (I. punctatus x I. furcatus) catfish following Bolbophorus damnificus infection - Mackenzie A. Gunn; Matt J. Griffin; Brian D. Ott; T. Graham Rosser; Lester H. Khoo; David J. Wise; Peter J. Allen (Aquaculture, 2023)

Inhibition of P2X7 receptors by Lu AF27139 diminishes colonic hypersensitivity and CNS prostanoid levels in a rat model of visceral pain - Roland G. W. Staal; Adarsh Gandhi; Hua Zhou; Manuel Cajina; Anne-Marie Jacobsen; Sara Hestehave; Allen Hopper; Suresh Poda; Gamini Chandresana; Stevin H. Zorn; Brian Campbell; Marta Segerdahl; et al. (Purinergic Signalling, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Can Stomach Content and Microbiomes of Tuna Provide Near Real-Time Detection of Ecosystem Composition in the Pacific Ocean? - Alejandro Trujillo-González; Teng Li; Joanne Potts; Simon Nicol; Valerie Allain; Sam C. Godwin; Elodie Vourey; Annie Portal; Brian Kumasi; Thomas Usu; Allen Rodrigo; Dianne Gleeson (Frontiers in Marine Science, 2022)
This preliminary study used DNA metabarcoding to test whether the stomach content and gut microbiome of tuna could be a viable near real-time monitoring tool for detecting composition and change in oceanic ecosystems. The gut content of skipjack ( Katsuwonus pelamis , n=55) and yellowfin tuna ( Thunnus albacares , n=46) captured in the Pacific Ocean during El Niño Southern Oscillation events (ENSO) between 2015-2017 were examined by high throughput sequencing and complemented by morphological assessments to identify fishes, crustaceans and cephalopods in the stomach content. Gut microbiome was examined solely by high throughput sequencing. Stomach content and gut microbiome were compared between tuna species, ENSO events and capture location using generalised linear models. The full model (tuna species, capture location and interaction with ENSO) best explained fish prey composition, while capture location and ENSO weakly explained the composition of crustaceans and cephalopods. Skipjack and yellowfin tuna captured near coastal areas (Longitude<170°W) showed a greater diversity of prey compared to fish captured in oceanic regions of the Pacific, while Thunnus albacares showed a much more diverse stomach content than K. pelamis (21 fish, eight cephalopods and six crustaceans). Fish captured during La Niña events showed higher prey diversity compared to fish captured during El Niño. Tuna species best explained differences in gut microbiome to the Phylum level, while no model explained gut microbiome differences to the Order or Family level. This preliminary study shows that capture location and ENSO events explained differences in stomach content of K. pelamis and T. albacares, while tuna species best explained gut microbiome assemblages to the Phylum level.

The early Eocene (48 Ma) Qaladeza trondhjemite formed by wet partial remelting of mafic crust in the arc-related Bulfat Igneous Complex (Kurdistan, Iraq): constraints on the timing of Neotethys closure - Allen Nutman; Sarmad Ali; Yousif Mohammad; Brian G. Jones; Qing Zhang (Arabian Journal of Geosciences, 2022)
Events in the tectono-magmatic framework of the Eocene Bulfat Igneous Complex in the Kurdistan region of northeastern Iraq are revealed through the integrated field, petrographic, geochemical and zircon petrography and U–Pb geochronology of the Qaladeza trondhjemite sheets that cut gabbros of the complex. The trondhjemite sheets are variably deformed, with the cataclasis of large plagioclase feldspars. The trondhjemites are albitic, and geochemical features such as strong enrichment of the light REE relative to the heavy REE and low Ti and REE content show that they did not form as late differentiates of a MORB-like source, but instead by hydrous partial melting of mafic rocks, possibly also involving some more evolved crustal source as well. Qaladeza trondhjemite oscillatory-zoned magmatic zircon has an age of 48.0 ± 0.6 Ma (95% confidence). These domains have been etched to form voids in the zircons, the walls of which have thin coatings of Th- and Ca-bearing species. Subsequent partial recrystallization of the zircons obliterated the voids and increased the Th/U of the recrystallized zircon, which mostly formed at 38.74 ± 0.74 Ma. The 48 Ma domains relate to recycling of mafic crust in a proto-arc tectonic setting and are congruent with Eocene proto-arc magmatic activity within the Neotethyan oceanic basin. The 39 Ma domains relate to later tectonic-induced recrystallisation events coeval with the closure of Neotethys resulting from the late Eocene collision between the Arabian plate and Eurasia in Kurdistan.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Conservation of Marine Foundation Species: Learning from Native Oyster Restoration from California to British Columbia - April D. Ridlon; Althea Marks; Chela J. Zabin; Danielle Zacherl; Brian Allen; Jeffrey Crooks; Gary Fleener; Edwin Grosholz; Betsy Peabody; Jodie Toft; Kerstin Wasson (Estuaries and Coasts, 2021)
Marine foundation species are critical to the structure and resilience of coastal ecosystems and provide key ecosystem services. Since many have suffered severe population declines, restoration of foundation species has been undertaken worldwide. The Olympia oyster ( Ostrea lurida ) is a foundation species, and the restoration of depleted populations is a priority for maintaining ecosystem function of estuaries along the west coast of North America. Here, we synthesize all native oyster restoration projects conducted from California, USA, to British Columbia, Canada, and analyze project goals, methods, and outcomes. Currently, restoration projects are spread unevenly across the species’ range, driven by locally varying goals and implemented with contrasting approaches. We highlight the value of regional strategic planning and decision support tools to evaluate project design and methods for restoration, including the selection of substrates and the targeted use of aquaculture. We recommend future investment in larger projects, which our analysis found were more cost-effective, but which have been relatively rare for this species. We also recommend that funders support monitoring over broader temporal and spatial scales than in the past to better characterize long-term effects of restoration on oyster populations and the services they provide beyond the project footprint. We found that most projects successfully supported native oysters and engaged local communities, and recommend similar efforts to continue to enhance understanding of Olympia oysters, which remain unfamiliar to many coastal residents. We believe that the results of this synthesis are broadly applicable to marine foundation species generally, and can inform restoration and conservation efforts worldwide.

Relating sinking and suspended microbial communities in the California Current Ecosystem: digestion resistance and the contributions of phytoplankton taxa to export - Bellineth Valencia; Michael R. Stukel; Andrew E. Allen; John P. McCrow; Ariel Rabines; Brian Palenik; Michael R. Landry (Environmental Microbiology, 2021)
Summary We used 16S, 18S, plastid and internal transcribed spacer (for Synechococcus strains) sequencing to quantify relative microbial abundances in water‐column samples and on sediment‐trap‐collected particles across an environmental gradient in the California Current Ecosystem (CCE) spanning a > 60‐fold range of surface chlorophyll. Most mixed‐layer dominant eukaryotes and prokaryotes were consistently underrepresented on sinking particles. Diatoms were the only phototrophic taxa consistently overrepresented. Even within this class, however, one genus ( Thalassiosira ) was a particle‐enriched dominant, while a similarly abundant species was poorly represented. Synechococcus was significantly enriched on sinking particles at only one of four sites, but clade I was disproportionately abundant on sinking particles throughout the region compared with clade IV, the euphotic‐zone co‐dominant. The most abundant microbes on particles across the CCE were organisms with distributional maxima close to the sediment‐trap depth (rhizarians), microbes associated with metazoans or sinking particles as a nutritional habitat (certain alveolates, Gammaproteobacteria) and organisms that resist digestive degradation of their DNA ( Thalassiosira , Synechococcus ). For assessing taxon contributions of phytoplankton to carbon export, our results highlight the need for sequence‐based quantitative approaches that can be used to integrate euphotic‐zone abundances, compute rates and account for taxon differences in preservation of sequence markers through trophic processing.

Projected climatic changes lead to biome changes in areas of previously constant biome - Brian Huntley; Judy R. M. Allen; Matthew Forrest; Thomas Hickler; Ralf Ohlemüller; Joy S. Singarayer; Paul J. Valdes (Journal of Biogeography, 2021)
Aim Recent studies in southern Africa identified past biome stability as an important predictor of biodiversity. We aimed to assess the extent to which past biome stability predicts present global biodiversity patterns, and the extent to which projected climatic changes may lead to eventual biome changes in areas with constant past biome. Location Global. Taxon Spermatophyta; terrestrial vertebrates. Methods Biome constancy was assessed and mapped using results from 89 dynamic global vegetation model simulations, driven by outputs of palaeoclimate experiments spanning the past 140 ka. We tested the hypothesis that terrestrial vertebrate diversity is predicted by biome constancy. We also simulated potential future vegetation, and hence potential future biome patterns, and quantified and mapped the extent of projected eventual future biome change in areas of past constant biome. Results Approximately 11% of global ice‐free land had a constant biome since 140 ka. Apart from areas of constant Desert, many areas with constant biome support high species diversity. All terrestrial vertebrate groups show a strong positive relationship between biome constancy and vertebrate diversity in areas of greater diversity, but no relationship in less diverse areas. Climatic change projected by 2100 commits 46%–66% of global ice‐free land, and 34%–52% of areas of past constant biome (excluding areas of constant Desert) to eventual biome change. Main conclusions Past biome stability strongly predicts vertebrate diversity in areas of higher diversity. Future climatic changes will lead to biome changes in many areas of past constant biome, with profound implications for biodiversity conservation. Some projected biome changes will result in substantial reductions in biospheric carbon sequestration and other ecosystem services.

A Model for Studying the Biomechanical Effects of Varying Ratios of Collagen Types I and III on Cardiomyocytes - Brian Roman; Shweta Anil Kumar; Shane C. Allen; Monica Delgado; Sabastian Moncayo; Andres M. Reyes; Laura J. Suggs; Ramana Chintalapalle; Chunqiang Li; Binata Joddar (Cardiovascular Engineering and Technology, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Flexible Manufacturing: The Future State of Drug Product Development and Commercialization in the Pharmaceutical Industry - Yash Kapoor; Robert F. Meyer; Brian K. Meyer; James C. DiNunzio; Akhilesh Bhambhani; Justin Stanbro; Kristin J. M. Ploeger; Erin N. Guidry; Gregory M. Troup; Adam T. Procopio; Allen C. Templeton (Journal of Pharmaceutical Innovation, 2021)

Global vegetation patterns of the past 140,000 years - Judy R. M. Allen; Matthew Forrest; Thomas Hickler; Joy S. Singarayer; Paul J. Valdes; Brian Huntley (Journal of Biogeography, 2020)
Aim Insight into global biome responses to climatic and other environmental changes is essential to address key questions about past and future impacts of such changes. By simulating global biome patterns 140 ka to present, we aimed to address important questions about biome changes during this interval. Location Global. Taxon Spermatophyta. Methods Using the LPJ‐GUESS dynamic global vegetation model, we made 89 simulations driven using ice‐core atmospheric CO 2 concentrations, Earth's obliquity, and outputs from a pre‐industrial and 88 palaeoclimate experiments run using HadCM3. Experiments were run for 81 time slices between 1 and 140 ka, seven ‘hosing’ experiments also being run, using a 1‐Sv freshwater flux to the North Atlantic, for time slices corresponding to Heinrich Events H0–H6. Using a rule‐based approach, based on carbon mass and leaf area index of the LPJ‐GUESS plant functional types, the biome was inferred for each grid cell. Biomes were mapped, and the extent and total vegetation biomass of each biome, and total global vegetation biomass, estimated. Results Substantial changes in biome extents and locations were found on all vegetated continents. Although the largest magnitude changes were in Eurasia, important changes were seen in tropical latitudes and the Southern Hemisphere. Total global extent of most biomes varied on multi‐millennial (orbital) time scales, although some (e.g. Tropical Raingreen Forest) responded principally to the c. 100‐kyr glacial–interglacial cycle and others (e.g. Temperate Broad‐leaved Evergreen Forest) mainly to the c. 20‐kyr precession cycle. Many also responded to millennial contrasts between stadial (‘hosing’) and interstadial climates, with some (e.g. Tropical Evergreen Forest) showing stronger responses than to the multi‐millennial changes. Main conclusions No two time slices had identical biome patterns. Even equivalent Holocene and last interglacial time slices, and the last and penultimate glacial maxima, showed important differences. Only a small proportion of global land area experienced no biome change since 140 ka; many places experienced multiple biome changes. These modelling experiments provided little evidence for long‐term biome stability.

Compositional turnover and variation in Eemian pollen sequences in Europe - Vivian A. Felde; Suzette G. A. Flantua; Cathy R. Jenks; Blas M. Benito; Jacques-Louis de Beaulieu; Petr Kuneš; Donatella Magri; Dorota Nalepka; Bjørg Risebrobakken; Cajo J. F. ter Braak; Judy R. M. Allen; Wojciech Granoszewski; et al. (Vegetation History and Archaeobotany, 2020)

The prevalence and impact of transient species in ecological communities - Sara J. Snell Taylor; Brian S. Evans; Ethan P. White; Allen H. Hurlbert (Ecology, 2018)
Transient species occur infrequently in a community over time and do not maintain viable local populations. Because transient species interact differently than non‐transients with their biotic and abiotic environment, it is important to characterize the prevalence of these species and how they impact our understanding of ecological systems. We quantified the prevalence and impact of transient species in communities using data on over 19,000 community time series spanning an array of ecosystems, taxonomic groups, and spatial scales. We found that transient species are a general feature of communities regardless of taxa or ecosystem. The proportion of these species decreases with increasing spatial scale leading to a need to control for scale in comparative work. Removing transient species from analyses influences the form of a suite of commonly studied ecological patterns including species–abundance distributions, species–energy relationships, species–area relationships, and temporal turnover. Careful consideration should be given to whether transient species are included in analyses depending on the theoretical and practical relevance of these species for the question being studied.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

The late spring Caribbean rain‐belt: climatology and dynamics - Theodore L. Allen; Brian E. Mapes (International Journal of Climatology, 2017)
This study examines the dynamics of late spring rainfall (the Early Rainy Season, ERS ) in the Caribbean region, in hopes of identifying mechanistic‐based predictors for low‐frequency climate modulations of the system. The subtropical Caribbean rain‐belt develops in May as seasonal warming proceeds. By July, the rain‐belt retreats north apparently following the westerlies and their vigorous synoptic disturbances. Daily climatology data suggest a physical definition of the Caribbean ERS as mid‐May to mid‐late June. Based on an examination of daily loops for several seasons, we hypothesize that rainfall occurs quasi‐randomly throughout tongues of air with sufficiently high (above 45–50 mm) precipitable water ( PW ). These moist airmasses are brought north from the deep tropics by low‐level southerlies, and typically bent over into SW‐NE bands by latitudinal shear of the westerlies. The low‐level flow that transports PW tongues is partly induced by upper‐level synoptic disturbances in the westerlies, but also involves the gentle persistent flow around a geographically anchored Panama Low. While forced ascent is sometimes active ahead of these upper‐level troughs, convective and mesoscale processes can produce rain wherever PW is sufficient. In summary, we hypothesize that rainfall hinges largely on the Lagrangian statistics of moist air tongues . Comparison is drawn between the Caribbean rain‐belt and its East Asian counterpart (Meiyu‐Baiu), and other mechanisms and diagnostics from that literature are discussed. Statistical prediction exercises, based on mechanistically chosen predictors, could both test hypotheses and aid local agricultural interests in the region.

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

A seven-gene expression panel distinguishing clonal expansions of pre-leukemic and chronic lymphocytic leukemia B cells from normal B lymphocytes - Brian A. McCarthy; Sophia Yancopoulos; Mike Tipping; Xiao-jie Yan; Xue Ping Wang; Fiona Bennett; Wentian Li; Martin Lesser; Santanu Paul; Erin Boyle; Carolina Moreno; Rosa Catera; et al. (Immunologic Research, 2015)

Characterizing avian survival along a rural‐to‐urban land use gradient - Brian S. Evans; Thomas B. Ryder; Robert Reitsma; Allen H. Hurlbert; Peter P. Marra (Ecology, 2015)
Many avian species persist in human‐dominated landscapes; however, little is known about the demographic consequences of urbanization in these populations. Given that urban habitats introduce novel benefits (e.g., anthropogenic resources) and pressures (e.g., mortality risks), conflicting mechanisms have been hypothesized to drive the dynamics of urban bird populations. Top‐down processes such as predation predict reduced survivorship in suburban and urban habitats, whereas bottom‐up processes, such as increased resource availability, predict peak survival in suburban habitats. In this study, we use mark–recapture data of seven focal species encountered between 2000 and 2012 to test hypotheses about the processes that regulate avian survival along an urbanization gradient in greater Washington, D.C., USA. American Robin, Gray Catbird, Northern Cardinal, and Song Sparrow exhibited peak survival at intermediate and upper portions of the rural‐to‐urban gradient; this pattern supports the hypothesis that bottom‐up processes (e.g., resource availability) can drive patterns of avian survival in some species. In contrast, Carolina Chickadee showed no response and Carolina and House Wren showed a slightly negative response to urban land cover. These contrasting results underscore the need for comparative studies documenting the mechanisms that drive demography and how those factors differentially affect urban adapted and urban avoiding species.

Wide-ranging phylogeographic structure of invasive red lionfish in the Western Atlantic and Greater Caribbean - John S. S. Butterfield; Edgardo Díaz-Ferguson; Brian R. Silliman; Jonathan W. Saunders; Dayne Buddo; Antonio A. Mignucci-Giannoni; Linda Searle; Aarin C. Allen; Margaret E. Hunter (Marine Biology, 2015)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

The skill of atmospheric linear inverse models in hindcasting the Madden–Julian Oscillation - Nicholas R. Cavanaugh; Teddy Allen; Aneesh Subramanian; Brian Mapes; Hyodae Seo; Arthur J. Miller (Climate Dynamics, 2015)

Dietary nano-chromium tripicolinate increases feed intake and decreases plasma cortisol in finisher gilts during summer - Alex Tsungyu Hung; Brian Joseph Leury; Matthew Allen Sabin; Cherie Louise Collins; Frank Rowland Dunshea (Tropical Animal Health and Production, 2014)

Characterisation of 9 polymorphic microsatellite markers for the Critically Endangered lemur leaf frog Agalychnis lemur - Alex Petchey; Andrew Gray; Claes Andrén; Tim Skelton; Brian Kubicki; Calvin Allen; Robert Jehle (Conservation Genetics Resources, 2014)

The genu effect on plantar flexor power - Brian H. Dalton; Geoffrey A. Power; Matti D. Allen; Anthony A. Vandervoort; Charles L. Rice (European Journal of Applied Physiology, 2013)

Predicting ecosystem stability from community composition and biodiversity - Claire de Mazancourt; Forest Isbell; Allen Larocque; Frank Berendse; Enrica De Luca; James B. Grace; Bart Haegeman; H. Wayne Polley; Christiane Roscher; Bernhard Schmid; David Tilman; Jasper van Ruijven; et al. (Ecology Letters, 2013)
As biodiversity is declining at an unprecedented rate, an important current scientific challenge is to understand and predict the consequences of biodiversity loss. Here, we develop a theory that predicts the temporal variability of community biomass from the properties of individual component species in monoculture. Our theory shows that biodiversity stabilises ecosystems through three main mechanisms: (1) asynchrony in species’ responses to environmental fluctuations, (2) reduced demographic stochasticity due to overyielding in species mixtures and (3) reduced observation error (including spatial and sampling variability). Parameterised with empirical data from four long‐term grassland biodiversity experiments, our prediction explained 22–75% of the observed variability, and captured much of the effect of species richness. Richness stabilised communities mainly by increasing community biomass and reducing the strength of demographic stochasticity. Our approach calls for a re‐evaluation of the mechanisms explaining the effects of biodiversity on ecosystem stability.

The tectonic evolution of a N eo‐ T ethyan ( E ocene– O ligocene) island‐arc ( W alash and N aopurdan groups) in the K urdistan region of the N ortheast I raqi Z agros S uture Z one - Sarmad A. Ali; Solomon Buckman; Khalid J. Aswad; Brian G. Jones; Sabah A. Ismail; Allen P. Nutman (Island Arc, 2013)
The W alash and N aopurdan groups are incorporated into the lower allochthonous thrust sheet in the I raqi Z agros S uture Z one ( IZSZ ). 40 A r– 39 A r dates on magmatic feldspar separates from both W alash and N aopurdan volcanic rocks indicate an E ocene– O ligocene age (43.01 ± 0.15 to 24.31 ± 0.60 M a). The W alash and N aopurdan groups form a thrust sheet that is structurally overlain by an upper allochthon of C retaceous arc‐related rocks (106–92 M a) now known as the H asanbag igneous complex (formerly known as the G emo– Q andil G roup). The W alash and N aopurdan lower allochthon is thrust over the foreland basin R ed B eds series. Volcanic and subvolcanic units in the W alash and N aopurdan groups were studied from the M awat, G alalah– C homan, L eren, and Q alander– S heikhan provinces. Most of these rocks are basaltic to andesitic for both the N aopurdan and W alash suites. The petrographic study shows that these rocks are affected by metamorphic alteration under greenschist facies conditions, but preserve primary porphyritic textures with some relict igneous plagioclase, pyroxene, and hornblende. The enrichments in LREE / HREE and high T h/ N b and N b/ Z r show that the W alash and N aopurdan rocks have distinct subduction‐related signatures: specifically island‐arc tholeiite for the N aopurdan and calc‐alkaline to alkaline for the W alash suites. Hence the W alash and N aopurdan suites are back‐arc and arc systems, respectively, that developed 43–24 M a. Accordingly, the IZSZ contains a full record of N eo‐ T ethys pre‐collision‐related volcanism in dual subduction settings, from the E arly C retaceous ( H asanbag igneous complex) to the E ocene– O ligocene ( W alash– N aopurdan suites). Final continent–continent collision started when the last of the N eo‐ T ethys O cean was subducted beneath the I ranian continent, resulting in its collision with the A rabian P late, probably during the M iddle M iocene. This reinforces a continuity of events along the entire edge of the A rabian P late from T urkey, through I raq and I ran, and into O man.

Species distribution models indicate contrasting late‐Quaternary histories for Southern and Northern Hemisphere bird species - Brian Huntley; Judy R. M. Allen; Phoebe Barnard; Yvonne C. Collingham; Phyllida R. Holliday (Global Ecology and Biogeography, 2013)
Aim To test the following hypotheses: that Fynbos species had more extensive distributions at the Last Glacial Maximum (LGM), extending onto the exposed ‘Agulhas Plain’; that genetically distinct British taxa could have persisted through the LGM on adjacent areas of exposed shelf. Location Southern Africa; Europe. Methods Climatic response surfaces were fitted for 14 Fynbos and two European birds. These models were used to hindcast species distributions for palaeoclimates simulated using a fully coupled atmosphere–ocean general circulation model. LGM annual net primary productivity (ANPP) of two plant functional types upon which the European birds depend were simulated using a dynamic vegetation model and compared with potential LGM bird distributions. Results Fynbos birds' potential LGM distributions mostly extended southwards onto the exposed Agulhas Plain and were consistently more extensive than at present. This contrasts with conventional expectations for temperate species based upon Northern Hemisphere evidence. North‐west European taxa potentially had LGM ranges on exposed shelf and ice‐free areas to the west and south‐west of the British Isles ice sheet. This is consistent with available genetic evidence, supporting the long‐standing hypothesis that these taxa persisted through the LGM in this region. In both regions, results allow the generation of new testable hypotheses about species evolution and palaeobiogeography. Main conclusions Bird species found today in the Fynbos probably had more extensive ranges under glacial conditions, with the potential ranges of many species extending onto the Agulhas Plain. Bird taxa restricted today to the British Isles probably survived the LGM with limited distributions on exposed shelf and ice‐free areas south‐west of the British Isles ice sheet. Areas of shelf exposed under glacial conditions are likely to have been important components of glacial distributions of species in both the Northern and Southern Hemisphere. The contrasting history of Northern and Southern Hemisphere species has important conservation implications, especially in relation to conserving intra‐specific genetic diversity.

Stochastic and deterministic drivers of spatial and temporal turnover in breeding bird communities - James C. Stegen; Amy L. Freestone; Thomas O. Crist; Marti J. Anderson; Jonathan M. Chase; Liza S. Comita; Howard V. Cornell; Kendi F. Davies; Susan P. Harrison; Allen H. Hurlbert; Brian D. Inouye; Nathan J. B. Kraft; et al. (Global Ecology and Biogeography, 2013)
Aim A long‐standing challenge in ecology is to identify the suite of factors that lead to turnover in species composition in both space and time. These factors might be stochastic (e.g. sampling and priority effects) or deterministic (e.g. competition and environmental filtering). While numerous studies have examined the relationship between turnover and individual drivers of interest (e.g. primary productivity, habitat heterogeneity, or regional – ‘gamma’ – diversity), few studies have disentangled the simultaneous influences of multiple stochastic and deterministic processes on both temporal and spatial turnover. If turnover is governed primarily by stochastic sampling processes, removing the sampling effects of gamma diversity should result in non‐significant relationships between turnover and environmental variables. Conversely, if deterministic processes govern turnover patterns, removing sampling effects will have little influence on turnover gradients. Here, we test these predictions. Location The United States. Methods Continental‐scale, multidecadal data were used to quantify spatial and temporal turnover in avian community composition within 295 survey routes. A series of regression and structural equation models were coupled with a null model to construct statistical models describing turnover patterns. Results Examining explanatory variables alone or in combination showed that spatial and temporal turnover increased together, decreased with primary productivity and increased with habitat heterogeneity. The relationships between turnover and all variables became weaker when sampling effects were removed, but relationships with primary productivity and habitat heterogeneity remained relatively strong. In addition, spatial turnover increased strongly with spatial gamma diversity after sampling effects were removed. Main conclusions Our results show that spatial and temporal turnover are related to each other through a stochastic sampling process, but that each type of turnover is further influenced by deterministic processes. The relative influence of deterministic processes appears, however, to decrease with primary productivity and increase with habitat heterogeneity across an east–west longitudinal gradient in North America.

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

Does phylogeny matter? Assessing the impact of phylogenetic information in ecological meta‐analysis - Scott A. Chamberlain; Stephen M. Hovick; Christopher J. Dibble; Nick L. Rasmussen; Benjamin G. Van Allen; Brian S. Maitner; Jeffrey R. Ahern; Lukas P. Bell‐Dereske; Christopher L. Roy; Maria Meza‐Lopez; Juli Carrillo; Evan Siemann; et al. (Ecology Letters, 2012)
Meta‐analysis is increasingly used in ecology and evolutionary biology. Yet, in these fields this technique has an important limitation: phylogenetic non‐independence exists among taxa, violating the statistical assumptions underlying traditional meta‐analytic models. Recently, meta‐analytical techniques incorporating phylogenetic information have been developed to address this issue. However, no syntheses have evaluated how often including phylogenetic information changes meta‐analytic results. To address this gap, we built phylogenies for and re‐analysed 30 published meta‐analyses, comparing results for traditional vs. phylogenetic approaches and assessing which characteristics of phylogenies best explained changes in meta‐analytic results and relative model fit. Accounting for phylogeny significantly changed estimates of the overall pooled effect size in 47% of datasets for fixed‐effects analyses and 7% of datasets for random‐effects analyses. Accounting for phylogeny also changed whether those effect sizes were significantly different from zero in 23 and 40% of our datasets (for fixed‐ and random‐effects models, respectively). Across datasets, decreases in pooled effect size magnitudes after incorporating phylogenetic information were associated with larger phylogenies and those with stronger phylogenetic signal. We conclude that incorporating phylogenetic information in ecological meta‐analyses is important, and we provide practical recommendations for doing so.

In situ rates of body growth and palp regeneration of a spionid polychaete following simulated sublethal predation - John Allen Matthews; Brian T. Hentschel (Marine Biology, 2012)

Mineral Carbonation as the Core of an Industrial Symbiosis for Energy‐Intensive Minerals Conversion - Geoffrey F. Brent; Daniel J. Allen; Brent R. Eichler; James G. Petrie; Jason P. Mann; Brian S. Haynes (Journal of Industrial Ecology, 2012)
Summary The longer term sustainability of the minerals sector may hinge, in large part, on finding innovative solutions to the challenges of energy intensity and carbon dioxide (CO 2 ) management. This article outlines the need for large‐scale “carbon solutions” that might be shared by several colocated energy‐intensive and carbon‐intensive industries. In particular, it explores the potential for situating a mineral carbonation plant as a carbon sink at the heart of a minerals and energy complex to form an industrial symbiosis. Several resource‐intensive industries can be integrated synergistically in this way, to enable a complex that produces energy and mineral products with low net CO 2 emissions. An illustrative hypothetical case study of such a system within New South Wales, Australia, has been constructed, on the basis of material and energy flows derived from Aspen modeling of a serpentine carbonation process. The synergies and added value created have the potential to significantly offset the energy and emission penalties and direct costs of CO 2 capture and storage. This suggests that greenfield minerals beneficiation and metals refining plants should consider closer integration with the power production and energy provision plants on which they depend, together with a carbon solution, such as mineral carbonation, as a critical element of such integration. Other sustainability considerations are highlighted.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Global Competency and Issues in Contemporary Education / Agroforestry - Susan Moore; Erin Sills; Lee Allen; Douglas Frederick; Frederick Cubbage; John Garland; Julie Lydick; Gordon Holley; Jodi Roberts; Stephen Grado; Zhu Ning; Shannon Fowler; et al. (Journal of Forestry, 2011)
34We performed a five year integrated research, extension and education project aimed at strengthening global competence of students and faculty through collaboration in forestry. We sought to improve our students' ability to cooperate, increase their understanding of global dynamics of forestry markets and enhance their knowledge of various approaches to forest management and conservation with Chile as the focus. The project had four key components: (1) facilitate faculty and student involvement in Chile through Spanish language training, a website, and visits by Chilean faculty; (2) support NC State faculty and student research and study in Chile through travel grants and study tours; (3) build on faculty sabbaticals in Chile by funding student research assistants; and (4) disseminate information from Chile through multiple channels to both the university and professional communities. The faculty exchange visits; graduate student research; and participation of NCSU students, faculty and staff in the study tours to Chile had substantial effects when the participants returned to the US and disseminated information about their experiences through both formal and informal mechanisms. Both students and faculty at NCSU are more aware of forestry research, policy and management in Chile. Faculty at NCSU and Chilean universities Universidad de Concepción and Universidad de Austral have established a strong basis for collaboration and are continuing to work together on funding proposals, research, and papers. Students who participated in the study tours learned about both the culture and forestry in Chile, including similarities, differences, and lessons for the US. This presentation will describe the activities, outcomes and ongoing impacts of the project.

Ontogeny of salinity tolerance and evidence for seawater-entry preparation in juvenile green sturgeon, Acipenser medirostris - Peter J. Allen; Maryann McEnroe; Tetyana Forostyan; Stephanie Cole; Mary M. Nicholl; Brian Hodge; Joseph J. Cech (Journal of Comparative Physiology B, 2011)

Needle Electrode-Based Electromechanical Reshaping of Cartilage - Cyrus T. Manuel; Allen Foulad; Dmitriy E. Protsenko; Ali Sepehr; Brian J. F. Wong (Annals of Biomedical Engineering, 2010)

Niche conservatism as an emerging principle in ecology and conservation biology - John J. Wiens; David D. Ackerly; Andrew P. Allen; Brian L. Anacker; Lauren B. Buckley; Howard V. Cornell; Ellen I. Damschen; T. Jonathan Davies; John‐Arvid Grytnes; Susan P. Harrison; Bradford A. Hawkins; Robert D. Holt; et al. (Ecology Letters, 2010)
The diversity of life is ultimately generated by evolution, and much attention has focused on the rapid evolution of ecological traits. Yet, the tendency for many ecological traits to instead remain similar over time [niche conservatism (NC)] has many consequences for the fundamental patterns and processes studied in ecology and conservation biology. Here, we describe the mounting evidence for the importance of NC to major topics in ecology (e.g. species richness, ecosystem function) and conservation (e.g. climate change, invasive species). We also review other areas where it may be important but has generally been overlooked, in both ecology (e.g. food webs, disease ecology, mutualistic interactions) and conservation (e.g. habitat modification). We summarize methods for testing for NC, and suggest that a commonly used and advocated method (involving a test for phylogenetic signal) is potentially problematic, and describe alternative approaches. We suggest that considering NC: (1) focuses attention on the within‐species processes that cause traits to be conserved over time, (2) emphasizes connections between questions and research areas that are not obviously related (e.g. invasives, global warming, tropical richness), and (3) suggests new areas for research (e.g. why are some clades largely nocturnal? why do related species share diseases?).

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Biological consequences of invasion by reed canary grass (Phalaris arundinacea) - Greg Spyreas; Brian W. Wilm; Allen E. Plocher; David M. Ketzner; Jeffrey W. Matthews; James L. Ellis; Edward J. Heske (Biological Invasions, 2010)

APPLICATIONS OF GODAE OCEAN CURRENT FORECASTS TO SEARCH AND RESCUE AND SHIP ROUTING - Fraser Davidson; Arthur Allen; Gary Brassington; Øyvind Breivik; Pierre Daniel; Masafumi Kamachi; Satoshi Sato; Brian King; Fabien Lefevre; Marion Sutton (Oceanography, 2009)

Taking species abundance distributions beyond individuals - Hélène Morlon; Ethan P. White; Rampal S. Etienne; Jessica L. Green; Annette Ostling; David Alonso; Brian J. Enquist; Fangliang He; Allen Hurlbert; Anne E. Magurran; Brian A. Maurer; Brian J. McGill; et al. (Ecology Letters, 2009)
The species abundance distribution (SAD) is one of the few universal patterns in ecology. Research on this fundamental distribution has primarily focused on the study of numerical counts, irrespective of the traits of individuals. Here we show that considering a set of Generalized Species Abundance Distributions (GSADs) encompassing several abundance measures, such as numerical abundance, biomass and resource use, can provide novel insights into the structure of ecological communities and the forces that organize them. We use a taxonomically diverse combination of macroecological data sets to investigate the similarities and differences between GSADs. We then use probability theory to explore, under parsimonious assumptions, theoretical linkages among them. Our study suggests that examining different GSADs simultaneously in natural systems may help with assessing determinants of community structure. Broadening SADs to encompass multiple abundance measures opens novel perspectives in biodiversity research and warrants future empirical and theoretical developments.

Pharmacological manipulations of interval timing using the peak procedure in male C3H mice - Fuat Balci; Elliot A. Ludvig; Jacqueline M. Gibson; Brian D. Allen; Krystal M. Frank; Bryan J. Kapustinski; Thomas E. Fedolak; Daniela Brunner (Psychopharmacology, 2008)

Reversible Secretion of Glycosaminoglycans and Proteoglycans by Cyclically Stretched Valvular Cells in 3D Culture - Vishal Gupta; Jennifer A. Werdenberg; Brian D. Lawrence; Joe S. Mendez; Elizabeth H. Stephens; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2008)

Effects of elevated CO 2 on the protein concentration of food crops: a meta‐analysis - DANIEL R. TAUB; BRIAN MILLER; HOLLY ALLEN (Global Change Biology, 2008)
Meta‐analysis techniques were used to examine the effect of elevated atmospheric carbon dioxide [CO 2 ] on the protein concentrations of major food crops, incorporating 228 experimental observations on barley, rice, wheat, soybean and potato. Each crop had lower protein concentrations when grown at elevated (540–958 μmol mol −1 ) compared with ambient (315–400 μmol mol −1 ) CO 2 . For wheat, barley and rice, the reduction in grain protein concentration was ∼10–15% of the value at ambient CO 2 . For potato, the reduction in tuber protein concentration was 14%. For soybean, there was a much smaller, although statistically significant reduction of protein concentration of 1.4%. The magnitude of the CO 2 effect on wheat grains was smaller under high soil N conditions than under low soil N. Protein concentrations in potato tubers were reduced more for plants grown at high than at low concentrations of ozone. For soybean, the ozone effect was the reverse, as elevated CO 2 increased the protein concentration of soybean grown at high ozone concentrations. The magnitude of the CO 2 effect also varied depending on experimental methodology. For both wheat and soybean, studies performed in open‐top chambers produced a larger CO 2 effect than those performed using other types of experimental facilities. There was also indication of a possible pot artifact as, for both wheat and soybean, studies performed in open‐top chambers showed a significantly greater CO 2 effect when plants were rooted in pots rather than in the ground. Studies on wheat also showed a greater CO 2 effect when protein concentration was measured in whole grains rather than flour. While the magnitude of the effect of elevated CO 2 varied depending on the experimental procedures, a reduction in protein concentration was consistently found for most crops. These findings suggest that the increasing CO 2 concentrations of the 21st century are likely to decrease the protein concentration of many human plant foods.

Structure and metal binding properties of ZnuA, a periplasmic zinc transporter from Escherichia coli - Liliya A. Yatsunyk; J. Allen Easton; Lydia R. Kim; Stacy A. Sugarbaker; Brian Bennett; Robert M. Breece; Ivan I. Vorontsov; David L. Tierney; Michael W. Crowder; Amy C. Rosenzweig (JBIC Journal of Biological Inorganic Chemistry, 2008)

Species abundance distributions: moving beyond single prediction theories to integration within an ecological framework - Brian J. McGill; Rampal S. Etienne; John S. Gray; David Alonso; Marti J. Anderson; Habtamu Kassa Benecha; Maria Dornelas; Brian J. Enquist; Jessica L. Green; Fangliang He; Allen H. Hurlbert; Anne E. Magurran; et al. (Ecology Letters, 2007)
Species abundance distributions (SADs) follow one of ecology’s oldest and most universal laws – every community shows a hollow curve or hyperbolic shape on a histogram with many rare species and just a few common species. Here, we review theoretical, empirical and statistical developments in the study of SADs. Several key points emerge. (i) Literally dozens of models have been proposed to explain the hollow curve. Unfortunately, very few models are ever rejected, primarily because few theories make any predictions beyond the hollow‐curve SAD itself. (ii) Interesting work has been performed both empirically and theoretically, which goes beyond the hollow‐curve prediction to provide a rich variety of information about how SADs behave. These include the study of SADs along environmental gradients and theories that integrate SADs with other biodiversity patterns. Central to this body of work is an effort to move beyond treating the SAD in isolation and to integrate the SAD into its ecological context to enable making many predictions. (iii) Moving forward will entail understanding how sampling and scale affect SADs and developing statistical tools for describing and comparing SADs. We are optimistic that SADs can provide significant insights into basic and applied ecological science.

Low-temperature acclimation of barley cultivars used as parents in mapping populations: response to photoperiod, vernalization and phenological development - Allen Limin; Ann Corey; Patrick Hayes; D. Brian Fowler (Planta, 2007)

Testing the generality of the trophic cascade paradigm for sea otters: a case study with kelp forests in northern Washington, USA - Sarah K. Carter; Glenn R. VanBlaricom; Brian L. Allen (Hydrobiologia, 2007)

Awareness of gynecologic surveillance in women from hereditary non-polyposis colorectal cancer families - Kathleen Yang; Brian Allen; Peggy Conrad; C. Bethan Powell; Jonathan Terdiman; Lee-may Chen (Familial Cancer, 2006)

Identification of quantitative trait loci and associated candidate genes for low-temperature tolerance in cold-hardy winter wheat - Monica Båga; Sanjay V. Chodaparambil; Allen E. Limin; Marin Pecar; D. Brian Fowler; Ravindra N. Chibbar (Functional & Integrative Genomics, 2006)

Low-temperature tolerance and genetic potential in wheat (Triticum aestivum L.): response to photoperiod, vernalization, and plant development - Allen E. Limin; D. Brian Fowler (Planta, 2006)

A time series analysis of the relationship of ambient temperature and common bacterial enteric infections in two Canadian provinces - Manon Fleury; Dominique F. Charron; John D. Holt; O. Brian Allen; Abdel R. Maarouf (International Journal of Biometeorology, 2006)

A comparison of the phenotype and genotype in adenomatous polyposis patients with and without a family history - Brindusa Truta; Brian A. Allen; Peggy G. Conrad; Vivian Weinberg; Glenn A. Miller; Rob Pomponio; Lara R. Lipton; Germano Guerra; Ian P. M. Tomlinson; Marvin H. Sleisenger; Young S. Kim; Jonathan P. Terdiman (Familial Cancer, 2005)

A new early Holocene cryptotephra from northwest Scotland - Patricia H. Ranner; Judy R. M. Allen; Brian Huntley (Journal of Quaternary Science, 2005)
Clarification of the temporal relationships amongst records of environmental change is dependent on accurate timescales. Event markers such as tephra layers are extremely important for constraining chronologies and providing tie points. In this report we present evidence of a previously unknown early Holocene Icelandic cryptotephra from a lake in northern Scotland—the ‘An Druim Tephra’. The calibrated radiocarbon age of 9560 cal. yr BP for this new cryptotephra makes it an important addition to the suite of cryptotephras now recorded from the last glacial termination and early Holocene in northwest Europe. In addition we report evidence in support of a ‘Younger Borrobol Tephra’ from Lateglacial sediments of Allerød age. Copyright © 2005 John Wiley & Sons, Ltd.

Brain mitochondrial injury in human immunodeficiency virus–seropositive (HIV+) individuals taking nucleoside reverse transcriptase inhibitors - Brian C Schweinsburg; Michael J Taylor; Omar M Alhassoon; Raul Gonzalez; Gregory G Brown; Ronald J Ellis; Scott Letendre; John S Videen; J Allen McCutchan; Thomas L Patterson; Igor Grant; the HNRC Group (Journal of NeuroVirology, 2005)

EVIDENCE FOR AN ISOBUTYLAMIDE ASSOCIATED WITH HOST-PLANT RESISTANCE TO WESTERN FLOWER THRIPS, Frankliniella occidentalis, IN CHRYSANTHEMUM - RONG TSAO; CHRIS H. MARVIN; A. BRUCE BROADBENT; MARTINA FRIESEN; WAYNE R. ALLEN; BRIAN D. MCGARVEY (Journal of Chemical Ecology, 2005)

David M. Johns's "Necessity of New Alliances": an Immediate Opportunity - Brian Czech; Pat Magee; David Trauger; Eugene Allen; Helen Hands (Conservation Biology, 2004)

Genotype and phenotype of patients with both familial adenomatous polyposis and thyroid carcinoma - Brindusa Truta; Brian A. Allen; Peggy G. Conrad; Young S. Kim; Terri Berk; Steven Gallinger; Bharati Bapat; Jonathan P. Terdiman; Marvin H. Sleisenger (Familial Cancer, 2003)

Genetic mapping of an insertional hydrocephalus-inducing mutation allelic to hy3 - Michael L. Robinson; Carl E. Allen; Brian E. Davy; William J. Durfee; Frederick F. Elder; Christopher S. Elliott; Wilbur R. Harrison (Mammalian Genome, 2002)

Allometric scaling of maximum population density: a common rule for marine phytoplankton and terrestrial plants - Andrea Belgrano; Andrew P. Allen; Brian J. Enquist; James F. Gillooly (Ecology Letters, 2002)
A primary goal of macroecology is to identify principles that apply across varied ecosystems and taxonomic groups. Here we show that the allometric relationship observed between maximum abundance and body size for terrestrial plants can be extended to predict maximum population densities of marine phytoplankton. These results imply that the abundance of primary producers is similarly constrained in terrestrial and marine systems by rates of energy supply as dictated by a common allometric scaling law. They also highlight the existence of general mechanisms linking rates of individual metabolism to emergent properties of ecosystems.

Genetic and molecular control of folate-homocysteine metabolism in mutant mice - Sheila Ernest; Benedicte Christensen; Brian M. Gilfix; Orval A. Mamer; Angela Hosack; Mitchell Rodier; Clemencia Colmenares; James McGrath; Allen Bale; Rudi Balling; David Sankoff; David S. Rosenblatt; et al. (Mammalian Genome, 2002)

Physical-chemical influences on vernal zooplankton community structure in small lakes and wetlands of Wisconsin, U.S.A. - Jeffrey M. Schell; Carlos J. Santos-Flores; Paula E. Allen; Brian M. Hunker; Scott Kloehn; Aaron Michelson; Richard A. Lillie; Stanley I. Dodson (Hydrobiologia, 2001)

Submillennial environmental fluctuations during marine Oxygen Isotope Stage 2: a comparative analysis of diatom and pollen evidence from Lago Grande di Monticchio, South Italy - Anja P. Nimmergut; Judy R. M. Allen; Viv J. Jones; Brian Huntley; Richard W. Battarbee (Journal of Quaternary Science, 1999)

Submillennial environmental fluctuations during marine Oxygen Isotope Stage 2: a comparative analysis of diatom and pollen evidence from Lago Grande di Monticchio, South Italy - Anja P. Nimmergut; Judy R. M. Allen; Viv J. Jones; Brian Huntley; Richard W. Battarbee (Journal of Quaternary Science, 1999)

Estimating past floristic diversity in montane regions from macrofossil assemblages - Judy R. M. Allen; Brian Huntley (Journal of Biogeography, 1999)
Summary The relationship between the diversity of higher plant macrofossils in surface sediments of lakes and the surrounding vegetation is examined in two mountain regions; Grødalen in central Norway and the south‐east Cairngorms in Scotland. Two lake sediment cores from each area were also analysed to examine vegetation history and to estimate changes in biodiversity through the Holocene. The diversity of present day vegetation in each region was estimated using both quadrat data and classified satellite images of the study areas. The mean surface sample macrofossil representation of species recorded in quadrats collected within 250 m of the lakes was c . 17%. This figure drops to only c . 2% when the satellite imagery of the same area is used to provide a maximal species list. The macrofossil data from the Norwegian cores show that deglaciation in this region occurred earlier on the mountain summit than in the valley and that the maximum tree line elevation was during the interval 9100–4400 14 C yr BP . In the Cairngorms the maximum tree line elevation was prior to c . 4500 14 C yr BP . The changes in higher plant diversity recorded at these sites through the Holocene show that c . 4000 14 C yr BP the reduction in the tree line resulted in decreased β‐diversity at higher altitudes but an increase at the lower altitude as the forest cover opened up. Under conditions of climatic warming it is likely areas that come to lie below the tree line will experience reduced diversity and that a permanent loss of biodiversity would result from a severe reduction in the area above the tree line.

Petrogenesis of isotopically unusual Pliocene olivine leucitites from Deep Springs Valley, California - Brian L. Beard; Allen F. Glazner (Contributions to Mineralogy and Petrology, 1998)

Bahamian coral reefs yield evidence of a brief sea-level lowstand during the last interglacial: Reply - Brian White; H. Allen Curran; Mark A. Wilson (Carbonates and Evaporites, 1998)

Macroscale Properties of Porous Media from a Network Model of Biofilm Processes - Brian J. Suchomel; Benito M. Chen; Myron B. Allen (Transport in Porous Media, 1998)

Bahamian coral reefs yield evidence of a brief sea-level lowstand during the last interglacial - Brian White; H. Allen Curran; Mark A. Wilson (Carbonates and Evaporites, 1998)

Network Model of Flow, Transport and Biofilm Effects in Porous Media - Brian J. Suchomel; Benito M. Chen; Myron B. Allen (Transport in Porous Media, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Reply: Redepositional or Climate Event in Iberia During the Boreal - JUDY R. M. ALLEN; BRIAN HUNTLEY; WILLIAM A. WATTS (Journal of Quaternary Science, 1997)

Reply: Redepositional or Climate Event in Iberia During the Boreal - JUDY R.M. ALLEN; BRIAN HUNTLEY; WILLIAM A. WATTS (Journal of Quaternary Science, 1997)

The vegetation and climate of northwest Iberia over the last 14,000 years - JUDY R. M. ALLEN; BRIAN HUNTLEY; WILLIAM A. WATTS (Journal of Quaternary Science, 1996)

Restriction endonuclease mapping and molecular cloning of the human herpesvirus 6 variant B strain Z29 genome - G. J. Lindquester; N. Inoue; R. D. Allen; J. W. Castelli; F. R. Stamey; T. R. Dambaugh; J. J. O'Brian; R. M. Danovich; N. Frenkel; P. E. Pellett (Archives of Virology, 1996)

Baroreceptor responses derived from a fundamental concept - Mona F. Taher; Albert B. P. Cecchini; Mark A. Allen; Sherif R. Gobran; Robert C. Gorman; Brian L. Guthrie; Kyle A. Lingenfelter; Sina Y. Rabbany; Philip M. Rolchigo; Julius Melbin; Abraham Noordergraaf (Annals of Biomedical Engineering, 1988)

Regulation of isocitrate lyase in a mutant of Rhodopseudomonas capsulata adapted to growth on acetate - Allen M. Nielsen; Brian J. Rampsch; Gary A. Sojka (Archives of Microbiology, 1979)